CHANGES IN THE ROLE OF TEACHERS IN IT-BASED MATHEMATICAL LEARNING IN DISRUPTION ERA - Novy Trisnani (Universitas Sebelas Maret, 2018)
Educational disruption is a change in the form of technological evolution that targets the education system, especially in the learning process that occurs in schools. Disruption in learning results in a shift in the role of students and teachers. As a result there is a shift in the role of students and teachers. The teacher's role shifts to being a mentor, facilitator, motivator, even inspirers develop imagination, creativity, character, and team work. However, a technology cannot create soul. The teacher's spirit familiarizes the professional attitude of the noble personality, humanist and exemplary. The role of the teacher in helping students is to create enjoyable learning, which gives space for the unique potential of every human child to grow, which builds three basic aspects of human skills to live in the digital era, namely having a balance of exercise, behavior (character), and a strong and persistent work ethic.